Emerging and Miscellaneous Protozoal Diseases - Marcondes, Mary [UNESP]; Kent, Marc; Howerth, Elizabeth W.; Sykes, Jane E. (Elsevier, 2022)
Rangeliosis • Cause: Rangelia vitalii, a protozoan parasite of the phylum Apicomplexa, class Aconoidasida, order Piroplasmida; phylogenetically close to the family Babesiidae. • First Described: 1908, in dogs from Brazil (Carini, 1908). • Affected Hosts: Domestic dogs and wild canids (the crab-eating fox Cerdocyon thous, and the pampas fox Lycalopex gymnocercus). • Geographic Distribution: South America, especially in the south and south-east of Brazil, Argentina, and Uruguay. • Mode of Transmission: Amblyomma aureolatum ticks. • Major Clinical Signs: Lethargy, inappetence, weakness, weight loss, fever, pallor, jaundice, splenomegaly, lymphadenomegaly, pelvic limb edema, and hemorrhagic disorders including persistent hemorrhage from the tips and external surface of the pinnae, nose (epistaxis), oral cavity (including hematemesis), venipuncture sites, and GI tract (hemorrhagic diarrhea). • Differential Diagnosis: Other tick-borne diseases (e.g., canine babesiosis and canine monocytic ehrlichiosis), leptospirosis, leishmaniosis, immune-mediated disorders. • Human Health Significance: There is no evidence that R. vitalii can infect humans. Amebiasis and Balantidiasis • Cause: Nonenteric (free-living) amebiasis in dogs is caused by organisms belonging to the genera Acanthamoeba and Balamuthia. Amebic keratitis caused by Acanthamoeba spp. has rarely been reported in companion animals. GI amebiasis in dogs is rare and caused by Entamoeba histolytica; balantidiasis is also rare and caused by Balantioides coli (formerly Balantidium coli). • Affected Hosts: Domestic dogs. • Geographic Distribution: Worldwide. • Mode of Transmission: Unclear, but inhalation (systemic disease) or ingestion (systemic or GI disease) from environmental sources are suspected. • Major Clinical Signs: The major clinical signs of canine systemic amebiasis are lethargy, inappetence, weakness, weight loss, fever, and a variety of neurologic signs. Rare cases of localized amebic keratitis have been described in dogs with chronic keratoconjunctivitis sicca treated with topical immunosuppressive drugs. GI amebiasis may be characterized by signs of large bowel diarrhea and inappetence. • Differential Diagnosis: Systemic amebiasis must be differentiated from other viral, bacterial, protozoal, and fungal pathogens that cause chronic progressive CNS signs; and noninfectious diseases of the CNS (see Chapter 129). Differential diagnoses for amebic keratitis include squamous cell carcinoma, leishmaniosis, and toxoplasmosis. GI amebiasis and balantidiasis must be differentiated from other subacute and chronic infectious and inflammatory causes of large bowel diarrhea. • Human Health Significance: GI ameba and Balantioides can cause mild to severe diarrhea in humans, and systemic ameba can cause life-threatening disease. However, there is no strong evidence for a role of companion animals in zoonotic transmission.
Keywords: Acanthamoeba; Amblyomma; Balamuthia; Naegleria; Rangelia; vector-borne disease